The effectiveness of teaching and learning process in outdoor 28 recreation management / Tan Chee Hian, Tham Yin Choong and Ong Swee Ling - Tan, Chee Hian; Tham, Yin Choong; Ong, Swee Ling (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2013)
This study was mainly venture into effectiveness of laboratory method in teaching and learning (T & L) process Outdoor course. Total of 23 males and 16 female adults involved voluntarily. Varies technique skills such as - Kayaking; Abseiling; Trekking and Navigating or compasses; Survival skills as well as Recreational Managing skills were performed in duration of 14 weeks. The respondents were undergone T & L process on these varies techniques hands - on practice for 3 hourly per session and per week. The final result showed descriptively all respondents were highly satisfied with the method used by course’s instructor with mean score above mean score 4 out of 5 Likert scale for every single techniques skill and overall satisfaction level of respondents toward this method showed statistically as: Orienteering (M = 4.52); Abseiling (M = 4.45); Camp craft (M = 4.36); Survival (M = 4.33); and Trekking with 4.31 mean score. Perhaps, the effectiveness of T & L which was used by the course’s instructor also with highly mean score of 4.25 which concluded all respondents satisfied with method regardless gender involved. Thus, the hypotheses of Ho2, Ho1 been rejected because one sample t- test showed there was significant differences mean score between Survival skill; Trekking; Abseiling; Camp craft and Orienteering with reading accordingly: t (39) = 40.676; p < .05; t (39) = 44.433; p < .05; t (39) = 44.179; p < .05; t (39) = 30.217; p < .05 and t (39) = 26.703; p < .05 respectively as well as highly correlated between the T & L process with gender t (39) = .343; p < .05. In addition, this study justified the laboratory exploration method was relevance and appropriate for outdoor recreation management and this fulfillment of the outcome based education perspective.